2005
DOI: 10.1038/sj.ejcn.1602293
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative mood in the elderly: the ZENITH study

Abstract: Objective: To assess the quality of positive and negative affect (mood) in an ageing European sample. Background: Mood quality has important implications for both physical and mental wellbeing. Poor quality moods are associated with deficits in the diverse areas of cognitive function, health, and social relationships. The ageing process presents a number of potential challenges to successful mood regulation that could have wider implications. Design and participants: The current study examines the quality of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
3
12
0
3
Order By: Relevance
“…The results are more evident when the zinc status indicates a deficiency of this trace element. In agreement with previous findings, which indicated that zinc is of benefit for psychological aspects in older adults Simpson et al 2005;McConville et al 2005), significant differences in zinc status and psychological dimensions were found among the five Countries herein considered.…”
Section: Discussionsupporting
confidence: 93%
“…The results are more evident when the zinc status indicates a deficiency of this trace element. In agreement with previous findings, which indicated that zinc is of benefit for psychological aspects in older adults Simpson et al 2005;McConville et al 2005), significant differences in zinc status and psychological dimensions were found among the five Countries herein considered.…”
Section: Discussionsupporting
confidence: 93%
“…Among women, lower serum zinc concentrations have been associated with the severity of postpartum depressive symptoms (57). However, another study in an aging European sample found no association between mood and zinc status; zinc status was within the normal range, which suggests that the potential influence of zinc on mood may be small and undetectable when zinc status is within normal limits (61). Lower plasma zinc concentrations were related to poorer results for several psychological variables, including measures of cognitive status, mood, and perceived stress, especially in areas with low zinc intakes and a limited variety of foods containing zinc (58,59).…”
Section: Community Samplesmentioning
confidence: 95%
“…It has, however, identified two exceptions to this trend among older participants in Italy and France. If nutritional supplementation is important for mood regulation, these two exceptions should provide good tests of efficacy (McConville et al, 2005).…”
Section: Psychological Parametersmentioning
confidence: 99%